BRUSHSTROKES AND BITES EXPLORING THE ARTISTIC FUSION OF FOOD AND COLORS IN INDORE, INSPIRED BY ARTIST WAYNE THIEBAUD - Jain, Pooja; Ukande, Anu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In a city known for its delectable street food and vibrant culinary culture, the artistry of Wayne Thiebaud, USA, has sparked an intriguing opportunity for artist Pooja Jain in Indore. This study explores the inspiration drawn from Thiebaud's iconic food paintings and the unexplored potential it offers to artists in the region. The research delves into both the conceptual aspects of creating food-themed art and the technical methods and principles that have fueled Thiebaud's success. This investigation comprises a twofold methodology: an in-depth analysis of Thiebaud’s artworks focusing on color palette, brushstroke techniques, and compositional elements, and the creation and analysis of the researcher's own paintings of Indore's street food. Additionally, a survey was conducted in Indore to capture local perceptions of the fusion of art and food. By examining Thiebaud’s thick paint strokes and bold use of color, creating original artworks, and surveying Indore’s residents about their views on food-themed art, this study aims to unearth untapped creative possibilities, fostering a dynamic conversation between the city's culinary prowess and its burgeoning art community.